Qualidade do leite e impacto econômico de diferentes tipos de coletas e condições de transporte da fazenda à indústria - Flavia Lopes Dionizio (2013)
The milk chain has a great importance in the Brazilian agribusiness. One step that markedly contributed to its improvement is the standardization of bulk milk tank collection by IN Nº 51/2002 and IN Nº 62/2011 and establishment of milk quality payment incentive programs by dairy industry. Thus, the present study aimed to evaluate the milk quality parameters submitted to different types of bulk milk tank collection and transport conditions from the farm to dairy industry. Here, 254 bulk milk tank samples and 35 raw milk samples from different transportation routes (15 milk samples from trucks that use traditional rotor collection with suction pump and 20 milk samples from trucks that use the modified vacuum method) were analyzed. The number of producers by route, distance traveled and time spent per route were significantly higher in the vacuum truck (P 0.05), although no significant difference in the milk quality parameters in both milk samples collected at dairy farms and dairy industry were found (P>0.05). The multivariate principal component analysis showed that the time spent and distance traveled from dairy farm to dairy industry were the most important variables that influence the behavior of others quality parameters. The total bacteria count (TBC) of raw milk at dairy farm was lower than those milk samples collected at dairy industry, although no significant difference in TBC was encountered between transport conditions (P 0.05). Furthermore, when we estimated the bonus payment by TBC applied by dairy industry, it was found that economic losses due TBC was 61.95% and 56.95% for rotor truck and vacuum trucks, respectively. Regarding, milk transportation changes are needed in supply chain logistic management in attempt to minimize losses to dairy industry.